Mutations in two distinct regions of acetolactate synthase regulatory subunit from Streptomyces cinnamonensis result in the lack of sensitivity to end-product inhibition - Kopecký, J; Janata, J; Pospísil, S; Felsberg, J; Spízek, J (Biochemical and biophysical research communications, 1999)
Acetolactate synthase small subunit encoding ilvN genes from the parental Streptomyces cinnamonensis strain and mutants resistant either to valine analogues or to 2-ketobutyrate were cloned and sequenced. The wild-type IlvN from S. cinnamonensis is composed of 175 amino acid residues and shows a high degree of similarity with the small subunits of other valine-sensitive bacterial acetolactate synthases. Changes in the sequence of ilvN conferring the insensitivity to valine in mutant strains were found in two distinct regions. Certain point mutations were located in the conserved domain near the N terminus, while others resulting in the same phenotype shortened the protein at V(104) or V(107). To confirm whether the described mutations were responsible for the changed biochemical properties of the native enzyme, the wild-type large subunit and the wild-type and mutant forms of the small one were expressed separately in E. coli and combined in vitro to reconstitute the active enzyme.
Keywords: klonování DNA; acetolaktátsynthasa; Allosteric Regulation; mutace; alosterická regulace; Recombinant Proteins; Valine; Amino Acid Sequence; molekulární sekvence - údaje; katalytická doména; sekvence aminokyselin; Escherichia coli; Base Sequence; Streptomyces; teplota; rekombinantní proteiny; Catalytic Domain; Molecular Sequence Data; Mutation; valin; sekvenční seřazení; zpětná vazba; substituce aminokyselin; Sequence Alignment; Feedback; Genes, Bacterial; Amino Acid Substitution; Temperature; Conserved Sequence; Acetolactate Synthase; mutační analýza DNA; bakteriální geny; bakteriální proteiny; konzervovaná sekvence; sekvence nukleotidů; DNA Mutational Analysis; Cloning, Molecular; Bacterial Proteins